Let "F(x,y,z,p,q)=2xz+q^2-x(xp+yq)=0."Then Charpit’s equations are
"=\\dfrac{dp}{-2z+yq}=\\dfrac{dq}{-qx}"
From the first and last equations, we get
Integrate
"q=ax, a=const."
Then the equation "F(x, y, z, p, q)=0" gives
"p=\\dfrac{2z+a^2x-ayx}{x}"
Hence the relation "dz=pdx+qdy" leads to
"=>d(\\dfrac{z}{x^2})+d(\\dfrac{a^2}{x})=ad(\\dfrac{y}{x})"
which, on integration, gives
"z+a^2x=axy+bx^2"
which is a complete integral, "b" being a constant.
Now we show that
"x(y + cx)^2 = 4(z \u2212 dx^2)\\ \\ \\ \\ \\ \\ \\ \\ \\ (1)"is also a complete integral.
Let us consider the curve Γ : "y=0, z=\\dfrac{c^2x^3+4dx^2}{4}" on the surface "(1)."
At the intersections of "z+a^2x=axy+bx^2" and the curve Γ we have
which has equal roots when "b=d\\pm ac." Taking "b=d+ac," the subsystem has the equation "z+a^2x=axy+(d+ac)x^2," i.e.
"a^2x-x(cx+y)a+(z-dx^2)=0"which has the envelope
i.e.
This is, therefore, a complete integral.
Comments
Leave a comment